Effects of Early Warning Score (EWS) on outcomes of inpatient services - Bobonera, Teguh Theryana; Pohan, Vivi Yosafianti; Mubin, Mohammad Fatkhul; Armiyati, Yunie (South East Asia Nursing Research, 2022)
The decrease in patient morbidity and mortality is influenced by quality inpatient services. Hospitalized patients can be in stable or unstable conditions. There is a phenomenon of patients whose condition is not stable being placed in inpatient, due to the limitations of the intensive care unit. These patients are at risk for worsening clinical conditions that increase morbidity and mortality. One of the efforts to improve quality related to patient safety in hospitals is the application of the Early Warning Score (EWS) including in inpatient installations. An early warning score is one of the assessment parameters in hospital accreditation and quality of care.  The aim of this literature review is to explain effects of early warning score (EWS) on outcomes of inpatient services. This study uses a literature study approach with a descriptive review type. The articles used are international with a range of years from 2011-2021. The databases used are Proquest, PubMed, and the Google Scholar search engine. Implementation of EWS has resulted in higher utilization of the rapid response system but a lower incidence of cardiopulmonary arrest; it is associated with lower mortality rates, and improved patient safety and clinical outcomes. The results obtained that there is a correlation between the EWS value with mortality but not with the length of stay. Research results related to the correlation of EWS with referrals to ICU/HCU and activation of code blue cannot be analyzed so that in the future a larger number of samples and case variations are needed. A clinical flow can be created in advance so that good patient management can be carried out if the EWS score is higher. An early Warning Score (EWS) can be used to predict the patient outcome which is an indicator of inpatient services.